2006
DOI: 10.2353/ajpath.2006.050400
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin Expression in Intratumoral Astrocytes Marks Tumor Progression in Gliomas Induced by Prenatal Exposure to N-Ethyl-N-Nitrosourea

Abstract: To better study early events in glioma genesis, markers that reliably denote landmarks in glioma development are needed. In the present study, we used microarray analysis to compare the gene expression patterns of magnetic resonance imaging (MRI)-localized N-ethyl-N-nitrosourea (ENU)-induced tumors in rat brains with those of uninvolved contralateral side and normal brains. Our analysis identified osteopontin (OPN) as the most up-regulated gene in glioma. Using immunohistochemistry we then confirmed OPN expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 51 publications
1
38
0
Order By: Relevance
“…Characterization of different phases may be significant in the identification of effective molecular targets. This ENUinduced glioma rat model is a suitable model to study stage specific alterations during the tumor progression [42]. In the present study, we studied the stage specific alterations of b-catenin/Tcf signaling at initiation (P90), promotion (P135) and progression stages (P180).…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of different phases may be significant in the identification of effective molecular targets. This ENUinduced glioma rat model is a suitable model to study stage specific alterations during the tumor progression [42]. In the present study, we studied the stage specific alterations of b-catenin/Tcf signaling at initiation (P90), promotion (P135) and progression stages (P180).…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of different phases may be significant in the identification of effective molecular targets. Recent study has indicated N-ethyl N-nitrosourea (ENU) induced rat model, as a suitable model to study stage specific alterations as evident by osteopontin expression during the tumor progression [4]. Heterogeneous or complex nature of gliomas is one of the limitations to understand the effective molecular targets.…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptional regulation of OPN is complex and involves multiple pathways, including AP-1, Myc, v-Src, Runx/CBF, TGF-β/BMPs/Smad/Hox, and Wnt/β-catenin/APC/GSK-3β/Tcf-4 (29). OPN expression has been found to correlate with tumor progression in astrocytoma with high levels in GBM (33)(34)(35). OPN levels detected by immunohistochemistry identified that high cytoplasmic OPN expression correlates with poor patient survival (36).…”
Section: Cancer Epidemiol Biomarkers Prev; 19(6) June 2010mentioning
confidence: 99%